Morphological Aspects of Myocardial Remodeling under Conditions of its Volume Overload - V. P. Zakharova; A. A. Balabai; L. O. Stechenko; O. A. Krykunov; O. V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Myocardial overload occurs in situations when one or another heart chamber receives excess blood during diastole. Most often it occurs as a result of insufficiency of aortic or atrioventricular valves. Changes in cardiomyocytes (CMs) are regarded as compensatory, and the way myocardial remodeling with volume overload passes into the stage of decompensation still remains unexplored.The aim. To determine the morphological signs of adaptation and maladaptation of the myocardium to its volume overload.Materials and methods. Four hearts obtained at autopsy from patients who died of heart failure due to mitral valve insufficiency were used for the microscopical examination. Histological specimens were stained with hematoxylin and eosin, picrofuxin according to Van Gieson, fuxelin according to Weigert, alizarin red S and MSB method modified by Zerbino-Lukasevich “orange-red-blue” (ORB). For the study by electron microscopy, the material was obtained during operations in 6 patients with dilated atria from the area of surgical access.Results and conclusions. The heart chambers volume overload is compensated by the increase in the size of their cavities due to the “longitudinal” hypertrophy of the CMs which is expressed by the increase in the number of sarcomeres in each myofibril. The compensation mechanism is limited by the ability of abruptly altered CMs to produce new sarcomeres. Decompensation of adaptive processes is manifested by: destruction of intermyocytic and interfiber connections in functional myocardial syncytium; desynchronization of CMs contraction; the effect of CMs “sliding” relative to each other with the damage of interstitial connective tissue; dilation of T-tubes of CMs with the subsequent calcium damage of cellular organelles; dissociation of CMs and myocardial fibrosis.